Action Plan in Developing Sea Turtle Conservation as Ecotourism Attraction in Sukamade, Meru Betiri National Park - Haryati, Jehan Ramdani; Putri, Jayarani Fatimah; Chairiyah, Nurul; Harris, Ali; Putri, Helen Aulia; Pamungkas, Ratih Nila (Journal of Indonesian Tourism and Development Studies, 2016)
Sukamade Coastal Area located in Meru Betiri National Park has particular object as ecotourism attraction, i.e. Sea Turtle. On the other hand, national park management use the cross subsidy from ecotourism activities to promote the conservation action plans for the survival of sea turtle. This study was aimed to formulate action plans to develop the sea turtle conservation as ecotourism attraction in Sukamade Coastal Area. Field observation was conducted to evaluate the current activities of the sea turtle conservation and ecotourism activities in Sukamade. Semi-structured interview and secondary data collection was also conducted to support the formulation of the action plan. Data was analyzed by SWOT method to be developed into action plan. Results showed that the management of sea turtle conservation and ecotourism activities in Sukamade Coastal Area has been attempted to meet the conservation concept for sea turtle but also beneficial for the ecotourism implementation. However, we recommend a long term and short term action plan for the sustainability of the sea turtle conservation and ecotourism activities in Sukamade Coastal area. It includes the mangrove restoration, sea turtle feed development, mapping of sea turtle distribution and migration, the use of up to date biotechnology, workshop on conservation management, and the development of research facility in the area. Additional to the current policy on sea turtle conservation and ecotourism activities, the action plan that we recommended were expected to improve the sustainability management in Sukamade Coastal Area. Keywords: Action Plan, conservation, ecotourism, Sea Turtle.